Disability as an Interpersonal Experience: A Systematic Review on Dyadic Challenges and Dyadic Coping When One Partner Has a Chronic Physical or Sensory Impairment - Bertschi, Isabella C.; Meier, Fabienne; Bodenmann, Guy (Frontiers in Psychology, 2021)
Chronically disabling health impairments affect an increasing number of people worldwide. In close relationships, disability is an interpersonal experience. Psychological distress is thus common in patients as well as their spouses. Dyadic coping can alleviate stress and promote adjustment in couples who face disabling health impairments. Much research has focused on dyadic coping with cancer. However, other health problems such as physical and sensory impairments are also common and may strongly impact couple relationships. In order to promote couples’ optimal adjustment to impaired health the identification of disability-related relationship challenges is required. Furthermore, ways in which dyadic coping with these challenges may benefit couples could inform researchers and practitioners how to support couples in coping with health impairments. Accordingly, the aims of this study were to systematically review dyadic challenges and dyadic coping when one partner has a chronically disabling physical or sensory impairment. Out of 873 articles identified through database searches, 36 studies met inclusion criteria. The disability-related dyadic challenges identified in the review were changed roles and responsibilities within the couple, altered communication, compromised sexual intimacy, and reduced social participation. These challenges were reported to burden both partners and the couple relationship. Dyadic adjustment benefitted from a we-perspective, i.e., when couples viewed the disability as a shared challenge and engaged in conjoint dyadic coping. The results suggest that patient/care recipient and partner/caregiver roles should be de-emphasized, and that disability should be recognized as an interpersonal experience.